The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/e24060820
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Fluctuations in a Quantum Battery Charged by a Repeated Interaction Process

Abstract: A repeated interaction process assisted by auxiliary thermal systems charges a quantum battery. The charging energy is supplied by switching on and off the interaction between the battery and the thermal systems. The charged state is an equilibrium state for the repeated interaction process, and the ergotropy characterizes its charge. The working cycle consists in extracting the ergotropy and charging the battery again. We discuss the fluctuating efficiency of the process, among other fluctuating properties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Furthermore, in [28,29], it was shown that equilibrium states with population inversion can be achieved.…”
Section: Thermodynamic Frameworkmentioning
confidence: 99%
“…Furthermore, in [28,29], it was shown that equilibrium states with population inversion can be achieved.…”
Section: Thermodynamic Frameworkmentioning
confidence: 99%
“…In these models both the environment and time are discretized: the environment is indeed represented by a discrete set of ancillas that interact with the systems sequentially at discrete times. We remark that CMs have already been employed as a tool for studying the behaviour of OQBs [32][33][34][35][36][37]. However in most of these works the stream of ancillas that constitutes the CM plays the role of the charger, except in [34] where it plays the role of the battery itself.…”
Section: Introductionmentioning
confidence: 99%